A Nosocomial Foodborne Outbreak of a VIM Carbapenemase-Expressing Citrobacter freundii. (15th January 2018) - Pletz, Mathias W; Wollny, Antje; Dobermann, Ute-Heike; Rödel, Jürgen; Neubauer, Svetlana; Stein, Claudia; Brandt, Christian; Hartung, Anita; Mellmann, Alexander; Trommer, Sabine; Edel, Birgit; Patchev, Vladimir; et al.
Abstract: Background: A foodborne outbreak of VIM carbapenemase-expressing Citrobacter freundii (CPC) occurred between February 2016 and June 2016 at a major university hospital in Germany. Methods: An explosive increase in CPC isolated from rectal swabs of patients during weekly routine screening led to the declaration of an outbreak. A hospital-wide prevalence screening was initiated as well as screening of all patients on admission and before transfer to another ward, canteen staff, patient rooms, medical and kitchen inventory, and food. Swabs were streaked out on selective plates. All CPC isolates were analyzed using mass spectrometry, and selected isolates were analyzed using whole-genome sequencing. Results: A total of 76 were identified; most were unrelated cases in different wards. The CPC was isolated from retained samples of prepared vegetable salads and puddings and from a mixing machine used to prepare these foods only after an overnight culture. The immediate ban on serving potential source food resulted in a sharp decline and finally disappearance of novel cases. Repeated testing of presliced vegetables showed a high degree of contamination with C. freundii without a carbapenemase, indicating a possible source. Conclusions: An explosive increase in carbapenemase-expressing Enterobacteriaceae contamination may have been caused by a foodborne source, and presliced vegetables should be taken into account as a putative pathogen repository. These findings underline the importance of appropriate cooling, transport, reheating, and distribution of meals and indicate that probing of nonorganic surfaces is limited by low sensitivity, which may be increased by additional overnight cultivation in appropriate media. Abstract : An environmental Citrobacter freundii strain carrying a VIM gene on an intI1 cassette caused a major hospital-wide outbreak with enteral colonization of 76 patients. The outbreak strain was traced to a food mixing machine in the central kitchen.